Does at‐home bleaching induce systemic oxidative stress in healthy subjects? - Akbari, M; Nejat, AH; Farkhondeh, N; Mehraban Moghadam, S; Hashemy, SI; Mohammadipour, HS (Australian dental journal, 2017)
Background At‐home bleaching is a technique characterized by the use of carbamide peroxide or hydrogen peroxide as a tooth‐whitening agent. However, no data exist regarding systemic safety of this technique. The aim of this study was to investigate the effect of at‐home bleaching on serum redox homeostasis. Methods Twenty‐nine healthy volunteers who requested tooth‐whitening participated in this study. Specified bleaching trays were fabricated for the maxilla and mandible arches. Each participant was given two syringes containing 9% hydrogen peroxide gel to use for 30 min/night for 14 nights consecutively. To evaluate the redox status, the serum concentrations of malondialdehyde (MDA), total antioxidant capacity (TAC) and pro‐oxidant–antioxidant balance (PAB) were measured. Blood samples were obtained in the morning prior to initiation of study and the morning after expiration of the bleaching period. The collected data were analyzed using Student's t‐test with 95% confidence interval. Results Twenty‐three subjects completed the study. MDA, PAB and TAC were significantly increased after the bleaching period (P = 0.001, 0.001 and 0.002, respectively). Conclusions At‐home bleaching revealed the potential to disturb oxidant–antioxidant balance and induce oxidative stress. Its clinical relevance is unfavourable and potential side‐effects of at‐home bleaching should be considered.